2014
DOI: 10.1002/ajmg.b.32218
|View full text |Cite
|
Sign up to set email alerts
|

A family study of trichotillomania and chronic hair pulling

Abstract: Little is known about the etiology of hair pulling (HP) and its relationship to other obsessive compulsive (OC) spectrum disorders. In a large-sample family study, we examined the familial aggregation of HP and co-transmission of obsessive compulsive disorder (OCD) and skin picking (SP). Our sample consisted of 110 proband cases with HP and 48 controls without HP, plus 128 first-degree case relatives and 50 first-degree control relatives. Case versus control relatives had higher recurrence risk estimates for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
1
25
1
1
Order By: Relevance
“…For example, in a family study of OCD patients that investigated the relationship of this condition with others -including behavioural addictions such as gambling disorder, trichotillomania and skin-picking disorder -it was found that any of these behavioural addictions occurred more frequently in first degree relatives of individuals with OCD, irrespective of whether or not cases also had the same diagnosis (Bienvenu et al 2000). The association may be strongest for trichotillomania; a family study investigating the familial aggregation of trichotillomania and co-transmission of OCD and skin-picking disorder suggested that relatives of individuals with trichotillomania had higher recurrence risk estimates for both trichotillomania and OCD (but not skin-picking disorder) compared to control relatives (Keuthen et al 2014). Based on these results, it was argued that there may be a familial subtype of trichotillomania related to OCD.…”
Section: Comorbiditymentioning
confidence: 99%
“…For example, in a family study of OCD patients that investigated the relationship of this condition with others -including behavioural addictions such as gambling disorder, trichotillomania and skin-picking disorder -it was found that any of these behavioural addictions occurred more frequently in first degree relatives of individuals with OCD, irrespective of whether or not cases also had the same diagnosis (Bienvenu et al 2000). The association may be strongest for trichotillomania; a family study investigating the familial aggregation of trichotillomania and co-transmission of OCD and skin-picking disorder suggested that relatives of individuals with trichotillomania had higher recurrence risk estimates for both trichotillomania and OCD (but not skin-picking disorder) compared to control relatives (Keuthen et al 2014). Based on these results, it was argued that there may be a familial subtype of trichotillomania related to OCD.…”
Section: Comorbiditymentioning
confidence: 99%
“…22,27,28 Moreover, it has been shown in two studies that first-degree relatives of individuals with chronic hair pulling have not only an increased risk for hair pulling disorders but also an increased risk for OCD, with recurrence risk estimates of 6.4% and 17%. 29,30 Moreover, one study showed that some relatives of probands with hair pulling and OCD also had both disorders, but no relatives of probands with only hair pulling had both disorders. The authors thus suggest that there may be familial subtypes of OCD that are particularly associated with certain other related disorders.…”
Section: Familial Recurrence Risk In Ocd and Related Disordersmentioning
confidence: 99%
“…Given elevated rates of comorbid axis I disorders in TTM vs. matched nonclinical controls 16 and the suggestion of higher rates of axis II disorders than expected by chance alone, 2 we hypothesized higher rates of neuroticism and lower rates of extraversion in those with TTM vs. matched controls. After controlling for affective variables, we expected there would no longer be any significant group differences in personality traits.…”
Section: Introductionmentioning
confidence: 99%